High affinity nucleic acid aptamers for streptavidin incorporated into bi-specific capture ligands. - Tahiri-Alaoui, A; Frigotto, L; Manville, N; Ibrahim, J; Romby, P; James, W (2002)
We have isolated 2'-Fluoro-substituted RNA aptamers that bind to streptavidin (SA) with an affinity around 7 +/- 1.8 nM, comparable with that of recently described peptide aptamers. Binding to SA was not prevented by prior saturation with biotin, enabling nucleic acid aptamers to form useful ternary complexes. Mutagenesis, secondary structure analysis, ribonuclease footprinting and deletion analysis provided evidence for the essential structural features of SA-binding aptamers. In order to provide a general method for the exploitation of these aptamers, we produced derivatives in which they were fused to the naturally structured RNA elements, CopT or CopA. In parallel, we produced derivatives of CD4-binding aptamers fused to the complementary CopA or CopT elements. When mixed, these two chimeric aptamers rapidly hybridized, by virtue of CopA-CopT complementarity, to form stable, bi-functional aptamers that we called 'adaptamers'. We show that a CD4-SA-binding adaptamer can be used to capture CD4 onto a SA-derivatized surface, illustrating their general utility as indirect affinity ligands.